TRANSFORMASI PENGGANTIAN PADA TEKS TERJEMAHAN AL-QURAN YANG MENGANDUNG ETIKA BERBAHASA - Markhamah .; Abdul Ngalim; Muinudinillah B; Atiqa Sabardila; Susilowati . (Kajian Linguistik dan Sastra, 2012)
This study aims to identify and describe the types of transformation replacements in the translation of the Quran which contain language ethics, and analyze their functions. The study involves descriptive qualitative method. The research object is the transformation replacements in the translation of the Quran which contain language ethics and their functions. In obtaining the data, field note and content analysis are applied. The data are analyzed by distributive and comparative techniques. The findings show that the types of transformation replacements in the translation of the Quran which contain language ethics include (1) the replacement of equal syntactic level, and (2) the replacement of smaller syntactic levels, from one to four levels. The transformation replacemnts in the translation of the Quran function to show language ethics including the replacement of linguistic units which clarify the participants (the first, second, and third speakers), and the replacement of linguistic units into shorter forms to make effective sentences.